Financial expenditures for rendering home medical and social care to lonely and lonely-residing elderly people - I. N. Moroz; T. G. Svetlovich; T. V. Kalinina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
Financial resources for rendering home medical and social care were split between the health care institutions (67.4 %), the territorial centers of social care (32.1 %) and the Visiting Nurses Service of BRCS with 0.5 % only.